Squished - Lloyd, Megan Wagner, ....-; Nutter, Michelle Mee, ....- (New York : Scholastic, 2023)
Eleven-year-old Avery Lee loves living in Hickory Valley, Maryland. She loves her neighborhood, school, and the end-of-summer fair she always goes to with her two best friends. But she's tired of feeling squished by her six siblings! They're noisy and chaotic and the younger kids love her a little too much. All Avery wants is her own room -- her own space to be alone and make art. So she's furious when Theo, her grumpy older brother, gets his own room instead, and her wild baby brother, Max, moves into the room she already shares with her clinging sister Pearl! Avery hatches a plan to finally get her own room, all while trying to get Max to sleep at night, navigating changes in her friendships, and working on an art entry for the fair. And when Avery finds out that her family might move across the country, things get even more complicated. Megan Wagner Lloyd and Michelle Mee Nutter have once again teamed up to tell a funny, heartfelt, and charming story of family, friendship, and growing up.
Keywords: Familie; Graphic novel